Comparative Study of Mini-implants versus Standard Implants in Orthodontic Anchorage for Space Closure - Sanjay Kumar Sahoo; Manjunath Chekka; Riddhi Chawla; Mohammed Nehal Naimatullah; K. Kumar Misra; Pradeep Kandikatla; M. C. Prashant (Wolters Kluwer Medknow Publications, 2024)
Background: In order to obtain satisfactory treatment outcomes, orthodontic space closure frequently requires trustworthy anchoring devices. Because they are easier to install and smaller than regular implants, mini-implants have become a viable option. The purpose of this study was to evaluate the effectiveness of regular implants versus mini-implants as orthodontic anchoring devices for closing gaps in a tertiary care context. Methods: A total of 100 patients who needed space closure were split into two groups at random and given regular implants (group B, n = 50) or mini-implants (group A, n = 50). The rate of space closure, anchoring loss, and patient pain were measured using visual analog scales as the primary end measures. Resonance frequency analysis was used to assess implant stability. Based on implant survival and the lack of peri-implant problems, success rates were calculated. Findings: Mini-implants showed much lower rates of patient pain (P < 0.001) and anchoring loss (P < 0.05) than normal implants; however, they did show comparable rates of space closure (P = 0.42). In addition, mini-implants had comparable success rates (P = 0.78) and greater implant stability (P < 0.01) when compared to normal implants. Conclusion: In conclusion, mini-implants have benefits in anchorage preservation, patient comfort, and implant stability over regular implants when used as orthodontic anchoring devices for space closure. They also offer equivalent effectiveness. These results provide credence to the use of mini-implants as practical substitutes in orthodontic practice.